DOES GENDER MATTER’S ON THE DECISION MAKING FOR THE TYPE OF DEBT FINANCING OF THE MANUFACTURING SMEs IN BANGLADESH? - Uddin, Md Mohan; Bhuiyan, Abul Bashar; Islam, M Faruque Ul; Akter, Rowshan (International Journal of Small and Medium Enterprises, 2023)
Fostering the appropriate Small and Medium Enterprises (SME) financing is one of the most crucial ways of facilitating their success as well as the progress of a developing country. For that purpose, it is necessary to understand the financing behavior of the decision makers in the SMEs. Despite the indication of the importance of owner-manager gender in making debt financing decision, the literature is scant and inconclusive. Hence, this paper intends to investigate whether the gender of manager or owner is associated with more debt financing for fixed asset financing or for working capital financing. This paper analyses the World Bank Enterprise Survey data of 756 small and medium manufacturing firms of Bangladesh. In addition to using descriptive statistics, this study employs both parametric and nonparametric tests of hypotheses, including the Mann-Whitney U test. The findings suggest that female ownership, but not the management, is associated with more debt financing for working capital needs. However, no conclusive evidence of the role of gender on debt financing for fixed assets is found.  The results support the theoretical evidence related to the interplay between gender and small firm capital and can arguably be explained as a result of females’ better access to short term microfinance, and gender-based screening errors of the lenders. Extension of research is suggested to uncover the reasons behind more debt financing by female owners for working capital needs. The findings imply that the policy makers may optimize the financial system so that female owners’ debt financing demand is conveniently met. In addition, lending organizations may attempt to target female-owned manufacturing SMEs of Bangladesh as their potential working capital loan customers. This paper is among the first studies in the developing, or at least in Bangladesh context to provide evidence on the association between gender of owner vs manager and the nature of debt financing of manufacturing SMEs.JEL Classification Codes: G320, D250, J160, M130.